Bringing light into darkness: A multiple baseline mixed methods case series evaluation of Augmented Depression Therapy (ADepT). (September 2019) - Dunn, Barnaby D.; Widnall, Emily; Reed, Nigel; Owens, Christabel; Campbell, John; Kuyken, Willem
Abstract: Two core features of depression are elevations in negative valence system (NVS) functioning and reductions in positive valence system (PVS) functioning. Existing psychological treatments have focused on the NVS and neglected the PVS, which may contribute to sub-optimal outcomes. The present mixed methods multiple randomised baseline case series preliminarily evaluates Augmented Depression Therapy (ADepT), a novel depression treatment targeting PVS and NVS disturbance, that aims both to reduce depression and enhance wellbeing. Eleven clinically depressed participants were recruited. Intensive time series analyses showed that 7/11 participants improved on both wellbeing and depression. Reliable and clinically significant improvement was observed for 9/11 participants on at least one of these outcomes (and also across a range of other PVS and NVS outcomes). Group level analyses showed significant pre to post change on all outcomes. Benchmarking analyses indicated these effect sizes were at least comparable (and for some PVS outcomes superior) to existing treatments. Gains were largely sustained over one-year follow-up. Qualitative interviews indicated ADepT was feasible and acceptable. These findings provide preliminary support for ADepT as a novel depression treatment. Further evaluation, directly comparing ADepT to existing treatments using randomised controlled trial designs, is now required. Highlights: A case series evaluated Augmented Depression Therapy (ADepT). ADepT targets disturbances in negative and positive valence systems. ADepT was acceptable to treatment resistant depressed clients. ADepT was effective at reducing depression and building wellbeing. ADepT may be superior to existing treatments at reducing anhedonia.